Valency of the noun neapykanta and words semantically related with it in contemporary Lithuanian (written) language - Čižik-Prokaševa, Veslava (Taikomoji kalbotyra, 2024)
Using methods of interpretation, descriptive analysis, grammatical analysis, semantic and lexical analysis, 657 sentences containing different forms of the noun neapykanta drawn from the Corpus of Contemporary Lithuanian Language were analysed. The research showed that the syntactic valency of the noun neapykanta differs significantly from that of the verb nekęsti. Specifically, the nominative and genitive cases governed by the verb nekęsti are replaced by the genitive and dative cases governed by the noun neapykanta.The findings indicate that the valency of neapykanta is influenced by the semantics and grammar of nouns within its minimal semantic field. For example, neapykanta, like priešiškumas, nemeilė, and netolerancija, requires a genitive and/or dative actant. Similar to priešiškumas and netolerancija, neapykanta can take a construction with atžvilgiu instead of the dative, and, like nemeilė and netolerancija, it can govern the genitive. Furthermore, like the verb nekęsti, neapykanta can govern a subordinate clause and a prepositional phrase with dėl. It can also, like priešiškumas and netolerancija, co-occur with an adjective that indicates the cause of hatred or construction with dėl, similar to the verb nekęsti. Additionally, neapykanta, like priešiškumas, nemeilė, and netolerancija, can emphasize the fact that sometimes the feeling is mutual. This is expressed by reciprocal anaphora (vienas kitam), constructions such as tarp + genitive or genitive and genitive, and adjectives abipusė, savitarpio, (genitive) tarpusavio.When the noun neapykanta is in agreement with a dative beneficient, it expresses an emotional relationship between two beings. However, it describes a person᾽s attitude towards an object or a concept, neapykanta agrees with the dative contentive. When a hateful person is mentioned or emphasized in a sentence, the noun neapykanta agrees with the genitive percipient. Hence, the noun neapykanta has the same semantic valency as the verb nekęsti and other nouns within its minimal semantic field.As is known, the verb nekęsti requires an agent, which can be either a person or a living thing. However, the collected examples of neapykanta show that the feeling of hatred is unique to humans (just like nemeilė and netolerancija). Nonetheless, hatred can be directed towards anything: people, animate and inanimate objects, or abstracts concepts.
Keywords: noun neapykanta; valency; lexical semantic field